(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The “New Turan” National Turkic Museum is a unique cultural project in the world that revives the thousand-year-old common history, culture and statehood of the Turkic peoples through modern immersive technologies (VR, AR, 3D-mapping, artificial intelligence). This museum, which will be built in Uzbekistan, will be called the “Louvre of the Turks” and is intended to become a new cultural center and economic locomotive of the Turkic world. The project will allow Uzbekistan to achieve its tourism and economic goals until 2030 (5-7 million tourists per year, 2 billion in revenue) much earlier than the established deadline - by 2028. The article details the museum’s departments, phased implementation plan, and strategic importance.